Motor and sensory alalia: diagnostic difficulties - M. Yu. Bobylova; A. A. Kapustina; T. A. Braudo; M. O. Abramov; N. I. Klepikov; E. V. Panfilova (Русский журнал детской неврологии)
Alalia is a speech disorder that develops due to organic brain damage in children with normal hearing and intelligence during the first three year of life. Systemic speech underdevelopment in alalia is characterized by violations in the phonetic, phonemic, lexical, and grammatical structure. Patients with alalia can also have non-speech related impairments, including motor (impaired movement and coordination), sensory (impaired sensitivity and perception), and psychopathological disorders. There are three types of alalia: motor, sensory, and mixed. Children with motor alalia have expressive language disorders, speech praxis, poor speech fluency, impaired articulation, and other focal neurological symptoms; however, they understand speech directed to them. Patients with motor alalia are often left-handed. Regional slowing and epileptiform activity are often detected on their electroencephalogram.  Children with sensory alalia are characterized by poor speech understanding (despite normal hearing) resulting in secondary underdevelopment of their own speech. These patients have problems with the analysis of sounds, including speech sounds (impaired speech gnosis), which prevents the development of association between the sound image and the object. Therefore, the child hears, but does not understand the speech directed at him/her (auditory agnosia). Differential diagnosis of alalia is challenging and may require several months of observation. It also implies the exclusion of hearing loss and mental disorders.